Adapting to transradial approach in cerebral angiography: Factors influencing successful cannulation. Issue 2 (April 2023) - Yaser Arafath, Mohamed; Bhatia, Vikas; Kumar, Ajay; Chauhan, Rajeev; Prabhakar, Anuj; Gupta, SK; Singh, Paramjeet
Background: To evaluate factors that influence the successful cannulation of intracranial vessels using a transradial approach. Methods: A total of 61 transradial diagnostic angiograms were evaluated in a tertiary care center from July 2020 to December 2021. We evaluated the learning curve and aortic arch vessel factors that may influence the cannulation of intracranial major vessels using a transradial approach. Results: Learning curve for the procedure was established after 21 cases. We were successful in cannulating the supra-aortic arteries except in 4 cases where we were unable to cannulate the left VA (vertebral artery). Significant positive correlation was seen between time to Sim (Simmons curve) formation and aortic arch diameter ( p = .002). Significant positive correlation was also seen between left VA take-off angle and time to cannulate left VA ( p = .001) and negative correlation was noted between left CCA (common carotid artery) take-off angle and time to cannulate left CCA ( p = .001). Conclusion: Transradial approach is a feasible and safe approach for performing cerebral angiography. Multiple factors can influence the procedure time and successful cannulation of intracranial vessels. With the availability of radial specific hardware in the future, procedural success and time taken to complete the procedure may improve.